Informing retention in longitudinal cohort studies through a social marketing lens: Raine Study Generation 2 participants' perspectives on benefits and barriers to participation - Costello, L.; Dare, J.; Dontje, M.; Straker, Leon (2020)
BACKGROUND: Longitudinal cohort studies have made significant contributions to medical discoveries and provide the impetus for health interventions which reduce the risk of disease. Establishing and maintaining these cohorts is challenging and costly. While some attrition is unavoidable, maintaining a sufficient number of participants ensures that results remain representative and free from bias. Numerous studies have investigated ways to reduce attrition but few studies have sought to understand the experience of participants, and none have examined this through a social marketing framework. This first paper in a two part-series describes participants' experiences according to: benefits, barriers, motivators and influencers. The second paper uses this understanding to address issues relating to the 4Ps (product, price, place, promotion) of social marketing.